2019
DOI: 10.1161/circulationaha.119.039573
|View full text |Cite|
|
Sign up to set email alerts
|

Genomics-First Evaluation of Heart Disease Associated With Titin-Truncating Variants

Abstract: Background-Truncating variants in the Titin gene (TTNtvs) are common in individuals with idiopathic dilated cardiomyopathy (DCM). However, a comprehensive genomics-first evaluation of the impact of TTNtvs in different clinical contexts, and evaluation of modifiers such as genetic ancestry, has not been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
91
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 37 publications
14
91
1
5
Order By: Relevance
“…In the present study, higher frequency of atrial fibrillation was a predictor for HF recurrence, supporting previous findings of HF risk factors . Sustained atrial fibrillation has also been strongly associated with atrial fibrosis, and a recent study indicated that genetic variants of TTN could cause atrial fibrillation . These findings suggest that cardiomyocyte degeneration can lead to myocardial fibrosis, although the effect is different between atrial and ventricular muscles.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, higher frequency of atrial fibrillation was a predictor for HF recurrence, supporting previous findings of HF risk factors . Sustained atrial fibrillation has also been strongly associated with atrial fibrosis, and a recent study indicated that genetic variants of TTN could cause atrial fibrillation . These findings suggest that cardiomyocyte degeneration can lead to myocardial fibrosis, although the effect is different between atrial and ventricular muscles.…”
Section: Discussionsupporting
confidence: 90%
“…In the context of manifest disease, family-based studies demonstrate the incomplete and variable penetrance of ICC variants [ 7 9 ]. While genotype-first approaches overcome the ascertainment bias inherent to case series and family-based studies, phenotypic features described are often derived from retrospective electronic medical records, lack specific ICC-targeted investigations, and hence may underestimate the magnitude of any effect [ 10 14 ]. The few reports of ICC SF disclosure highlight challenges with interpreting variants and correlating them with clinical findings and family history, and with patient management [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association of Titin variants and dilated cardiomyopathy in individual of African ancestry has been reported as weak. 12 Liver disease was only documented in 24.5% of patients with ACM in our study group, with minimal hyperbilirubinemia noted in this group, possibly a reflection of some decrease in the hepatic excretory function. In this regard, the relationship between liver cirrhosis from alcohol in patients with ACM has been controversial; 1 however, a prospective study documented that cirrhosis was present in 43% of patients with ACM.…”
Section: Discussionmentioning
confidence: 51%